1-Hexyl n-cyanoacrylate compound (Neucrylate™ AN), a new berry aneurysm treatment. II. Rabbit implant studies: technique and histology. (8th June 2011) - Kerber, Charles W; Pakbaz, Ramin Sean; Hasteh, Farnaz; Miskolczi, Laszlo; Lieber, Barry Baruch
Abstract : Introduction: Following satisfactory benchtop testing of a new liquid embolic agent, animal implant studies were performed. Materials and method: Elastase aneurysms were created in the right common carotid artery of New Zealand rabbits under approved institutional guidelines. Using direct fluoroscopic control and commercially available microcatheters, the device was introduced into the aneurysms. At 2 months, 12 months and 24 months, follow-up angiography was performed and analyzed. The animals were sacrificed, the brachiocephalic arteries were explanted and fixed, and the histologic appearance of the treated aneurysms was evaluated. Results: The Neucrylate polymerized into an open pore elastic sponge. The open pores permitted fibrous tissue ingrowth. By 2 months, all of the aneurysm necks had been covered by fibrous tissue and a neointima. Two of the aneurysms originally inadequately filled allowed opportunity for retreatment. The reactive change within the aneurysms demonstrated fibroblastic proliferation, collagen and some giant cells but no vascular necrosis. Results at 2 months, 12 months and 24 months were for all practical purposes similar. Conclusion: The lack of necrosis, the mild inflammatory response and the permanence of the implant are interesting in a cyanoacrylate based embolic agent, especially in light of the experience with lower chain homologs and other liquid embolic agents.